One night of partial sleep deprivation impairs recovery from a single exercise training session - Rae, D. E.; Chin, T.; Dikgomo, K.; Hill, L.; McKune, A. J.; Kohn, T. A.; Roden, L. C. (European Journal of Applied Physiology, 2017)
Purpose: The effects of sleep deprivation on physical performance are well documented, but data on the consequence of sleep deprivation on recovery from exercise are limited. The aim was to compare cyclists` recovery from a single bout of high-intensity interval training (HIIT) after which they were given either a normal night of sleep (CON, 7.56 ± 0.63 h) or half of their usual time in bed (DEP, 3.83 ± 0.33 h). Methods: In this randomized cross-over intervention study, 16 trained male cyclists (age 32 ± 7 years), relative peak power output (PPO 4.6 ± 0.7 W/kg) performed a HIIT session at ±18:00 followed by either the CON or DEP sleep condition. Recovery from the HIIT session was assessed the following day by comparing pre-HIIT variables to those measured 12 and 24 h after the session. Following a 2-week washout, cyclists repeated the trial, but under the alternate sleep condition. Results: PPO was reduced more 24 h after the HIIT session in the DEP (Delta0.22 ± 0.22 W/kg; range -0.75 to 0.1 W/kg) compared to the CON condition (Delta05 ± 0.09 W/kg, range -0.19 to 0.17 W/kg, p = 0.008, d = -2.16). Cyclists were sleepier (12 h: p = 0.002, d = 1.90; 24 h: p = 0.001, d = 1.41) and felt less motivated to train (12 h, p = 0.012, d = -0.89) during the 24 h recovery phase when the HIIT session was followed by the DEP condition. The exercise-induced 24 h reduction in systolic blood pressure observed in the CON condition was absent in the DEP condition (p = 0.039, d = 0.75). Conclusions: One night of partial sleep deprivation impairs recovery from a single HIIT session in cyclists. Further research is needed to understand the mechanisms behind this observation.